Problems Confronting Shea Butter Industry in Nigeria - Kabiru, Sanusi Mohammed; Fadeke, Adeloye Florence; Adegbemi, Adegebo Samson (International Journal of Sustainable Agricultural Research, 2018)
The Shea sector of the Nigeria economy has the potential to generate wealth and employment for large number of people at the same time. However, this is yet to be seen as the industry is currently underexploited. This could be attributed to many problems affecting the entire value chain of the industry. The study reviewed the literatures as well as authors experiences on the field using participatory tools like in-depth interview, focus group discussion and observations to identify the problems confronting the entire Shea butter industry and proffer solutions to them. The problems identified by the study includes indiscriminate cutting of Shea trees, lack of storage facilities for the kernel and butter, poor quality butter produced, lack of modern processing technology, poor infrastructural facilities like road, electricity and water. Others are lack of access to market, no credit facilities and, lack of government assistance and seasonality of Shea kernel. The study recommended that relevant government agencies should provide an enabling environment such as water, electricity, modern processing technologies, storage facility, good roads and make by-laws to stop indiscriminate cutting down of Shea trees to ensure sustainability of the Shea industry. Bank of industry and commercial banks should give out loan to Stakeholders along the value chain line to stimulate Shea butter production. The stakeholders in the industry should also form functional cooperatives to collectively solve their problems.